Oh, hi! [videorecording (DVD)] - Brooks, Sophie (Director); Gordon, Molly, 1994-; Lerman, Logan, 1992-; Viswanathan, Geraldine, 1995-; Reynolds, John, 1991- (Sony Pictures Home Entertainment, 2025)
Iris and Isaac's first romantic weekend getaway as a couple goes awry. Convinced she's met her perfect guy and that he's just confused; Iris goes to increasingly ridiculous and irrational lengths to prove to Isaac that they are meant to be together.